2002
DOI: 10.1177/104973202129120313
|View full text |Cite
|
Sign up to set email alerts
|

Leveling the Playing Field? Exploring the Merits of the Ethics-as-Process Approach for Judging Qualitative Research Proposals

Abstract: There has been a recent growth in claims that qualitative research proposals are not treated equitably by ethics committees. In response, recent arguments centered on establishing the ethics of qualitative research, in the eyes of ethics committees, have indicated the need for an "ethics-as-process" approach. Accordingly, in this article, the authors illustrate the merits of this approach and provide three examples from the field: the outcomes of participating in qualitative interviews, sensitive handling of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 29 publications
4
90
0
9
Order By: Relevance
“…In addition, because ethnographic research is not a one-off event or discrete episode, consent is more often seen as a process, an ongoing contract of negotiation, as experiences develop in the field (Cutcliffe & Ramcharan, 2002;de Laine, 1997;Murphy & Dingwall, 2007). Essentially, the researcher often does not know in advance the course the research will take, making it difficult to outline the full nature of the research, as requested by HRECs (Cutcliffe & Ramcharan, 2002;Karnieli-Miller et al, 2009).…”
Section: Consent In Ethnographic Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, because ethnographic research is not a one-off event or discrete episode, consent is more often seen as a process, an ongoing contract of negotiation, as experiences develop in the field (Cutcliffe & Ramcharan, 2002;de Laine, 1997;Murphy & Dingwall, 2007). Essentially, the researcher often does not know in advance the course the research will take, making it difficult to outline the full nature of the research, as requested by HRECs (Cutcliffe & Ramcharan, 2002;Karnieli-Miller et al, 2009).…”
Section: Consent In Ethnographic Researchmentioning
confidence: 99%
“…Essentially, the researcher often does not know in advance the course the research will take, making it difficult to outline the full nature of the research, as requested by HRECs (Cutcliffe & Ramcharan, 2002;Karnieli-Miller et al, 2009). Qualitative methodologies are emergent, adaptive, and less predictable than biomedical research methodologies (Cutcliffe & Ramcharan, 2002;Flick, 2009;Katz, 2006), therefore setting out precise written consent forms can be problematic, but it does not then follow that the study is ipso facto unethical (de Laine, 1997).…”
Section: Consent In Ethnographic Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Recognising that our research participants are often marginalised in a range of ways, and that the research could be identified with intervention services, we have implemented strategies to ensure that gaining informed consent has been an ongoing, renegotiable process. Cutcliffe & Ramcharan (2002) refer to this as 'process-consent'.…”
Section: Engaging With Familiesmentioning
confidence: 99%